Tracking of Brain Tumors using Vision and Neurosonography - Rubén Machucho Cadena; Sergio de la Cruz Rodríguez; Eduardo Bayro-Corrochano (Applied Bionics and Biomechanics)
We have developed a method to render brain tumours from endoneurosonography. We propose to track an ultrasound probe in successive endoscopic images without relying on an external optic or magnetic tracking system. The probe is tracked using two different methods: one of them based on a generalised Hough transform and the other one based on particle filters. By estimating the pose of the ultrasound probe in several contiguous images, we use conformal geometric algebra to compute the geometric transformations that yield the 3D position of the tumour, which was segmented in the ultrasound image using morphological operators. We use images from brain phantoms to evaluate the performance of the proposed methods, and our results show that they are robust.